Academic Conflicts in Research articles Discussion; A Comparative Study of Research Articles Written by Indonesian and International Authors in High Impact Journals of Applied Linguistics - Hardiah, Mei; Safnil, Safnil; Wardhana, Dian Eka Chandra (Proceeding International Conference on Malay Identity, 2024)
Criticizing others research in discussion section of research article is important to show the writers confidence in presenting the result of their research. However, it has not really noted by Indonesian writers. This recent research is aimed at finding the use of ACUs as the strategies to refer to others result in discussion section of research articles write in Bahasa Indonesia and in English by international writers in the field of linguistics and literature. 40 RADs were analysed to find out the ACUs used in RADs and the linguistics features of each units. The analysis is based on the Academics Conflict Units framework proposed by Sadeghie and Alinasab : 2020. The result revealed that the ACUs used in the RADs is different in number between the same field of study in different language used. In linguistics study the occurrences is quite similar in number but different in the type of ACUs used. Interestingly in literature study, Indonesian writers used more ACUs than international writers but both Indonesian and International writers only used Proposing Claims as the strategy to present their findings. It might due the different research area and topic of each research. These findings offer theoretical and pedagogical insight into the academic writing (especially research articles writing) instruction for Indonesian. Since the corpus of the data were only 40 RADs, further research with larger corpus of the data will be beneficial to get general pattern of ACUs used in RADs.